Prove that for the DSA:

(αe1 βe2 mod p) mod q = (αk mod p) mod q

To prove this, we need to show that:

(αe1 βe2 mod p) mod q = (αk mod p) mod q

First, let's expand the left side of the equation:

(αe1 βe2 mod p) mod q = ((α^e1 mod p) (β^e2 mod p)) mod q

Since e1 = k and e2 = 1 (based on the definition of the DSA), we can rewrite this as:

((α^k mod p) (β mod p)) mod q

Since β is usually a constant in the DSA algorithm (g^x mod p), we can simplify this further:

(α^k (g^x mod p)) mod q

Now let's expand the right side of the equation:

(αk mod p) mod q

This can be simplified to:

(α^k mod p) mod q

Therefore, we have shown that:

(αe1 βe2 mod p) mod q = (αk mod p) mod q

Hence, we have successfully proved that for the DSA, the equation holds true.